Improving the design of landscaped land for irrigation of drylands with the help of natural rainfall. (in the case of Navoi region). - Norpo’latov Maxsudjon Maxmudovich (Zien Journals, 2022)
Landscape planning opportunities in the field of agricultural land use are defined by legislative acts at the state level. Such legislative acts include the Land Code of the Republic of Uzbekistan. It defines land relations as land use and protection relations, ensuring equality of land use and protection concepts in all articles of the Land Code. Nevertheless, the use of landscape planning methods in land planning allows for the correct assessment of the available land potential and functional zoning. In this case, it is appropriate to carry out regionalization by separating lands of different nature, taking into account their differences in quality
Keywords: landscape; relief; layer; anthropogenic